MANAGEMENT OF PUBLIC SERVICES IN THE OFFICE OF THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF MAKASSAR CITY - Junaidin; Wahyuli, Sri; bima, taufik (Sekolah tinggi ilmu ekonomi pemuda, 2021)
Abstract Public services are an important part to consider in the development of autonomy because in addition to being in accordance with the basic reforms in the field of government, as well as directly related to the welfare of the community, service to the community has become the main objective in the implementation of public administration. By presenting a bus car as a Mobile Population and Civil Registration unit, it can reach people who are constrained by distance, and travel costs, as a concrete configuration of services provided by public service providers to accelerate services without having to go to the relevant Office to make submissions. application for the issuance of population documents and civil registration. There is a statement of attitude given by the Department of Population and Civil Registration of Makassar City in the form of a declaration which reads